The brown rot fungi of fruit crops (Monilinia spp.): II. Important features of their epidemiology (Review paper) - Holb, I. J. (International Journal of Horticultural Science, 2004)
Plant disease epidemiology provides the key to both a better understanding of the nature of a disease and the most effective approach to disease control. Brown rot fungi (Monilinia spp.) cause mainly fruit rot, blossom blight and stem canker which results in considerable yield losses both in the field and in the storage place. In order to provide a better disease control strategy, all aspects of brown rot fungi epidemiology are discribed and discussed in the second part of this review. The general disease cycle of Monilinia fructigena„M. laxa, M. fructicola and Monilia polystroma is described. After such environmental and biological factors are presented which influence the development of hyphae, mycelium, conidia, stroma and apothecial formation. Factors affecting the ability of brown rot fungi to survive are also demonstrated. Then spatio-temporal dynamics of brown rot fungi are discussed. In the last two parts, the epidemiology of brown rot fungi was related to disease warning models and some aspects of disease management.